Pengatur Kecepatan Prototipe Mesin Solenoid 4 Induktor Menggunakan Metode Kontrol Frekuensi - Hilal, Yusuf Nurul; Andromeda, Trias; Handoko, Susatyo (Universitas Semarang, 2021)
The development of electric vehicles is in rapid progress, especially in terms of the main engine drive. The use of solenoid can be applied as an alternative driving electric vehicles instead of a dc motor as the main driver. In this paper, the prototype solenoid machine is applied by using 4 inductors controlled by an Arduino microcontroller and the solenoid driver based on application of Mosfet L298N. The prototype runs successfully. Based on the experimental results, the greater the frequency value applies to the driver, the faster the solenoid moves. The acceleration occures due to the electromagnetic field which is getting stronger and the field is proportional to the frequency value, so the solenoid movement is faster.